Practice based research: a process approach in arts (Revista Electrónica REDINE, 2018)
The following research has as a main purpose to show the philosophical and methodological foundations of Practice Based Research in arts. So that the research is documentary, based mainly on the inductive view of the creation processes in the field of fine arts. Besides, the methodology used in the analysis of the sources and the organization of the text is Discourse Analysis, focusing on an interpretative perspective. For addressing the speech, three criteria are established: philosophical foundations, methodological foundations, and contrast with the human sciences for addressing the speech. It is important to say that the interpretation of the information obtained can show the importance of the comprehension about creative processes in arts.
Keywords: research; practice- philosophy; methodology